A Mobile Based Accounting Application Design for MSMEs using the RAD Method - Mashud, Mashud; Aisa, Sitti; Awaliah, Neneng; Rahman, Fery Fadul (TIN: Terapan Informatika Nusantara, 2025)
Digital transformation in the Micro, Small, and Medium Enterprises (MSMEs) sector has become a strategic necessity to improve the efficiency and transparency of financial management. This study aims to design and test a mobile-based accounting system that can support the digital recording, reporting, and financial management processes of MSMEs. The method used is Research and Development (R&D) with the Waterfall model, which includes the stages of needs analysis, system design using the Unified Modeling Language (UML) and functional testing using the Black Box Testing method. The results of the study indicate that all main features, including user registration, transaction recording, automatic reports, and multi-user management, function validly and according to functional specifications. Thus, the system can meet the basic accounting needs of MSMEs with a simple interface and real-time access via mobile devices. Practically, the results of this study produce a prototype of a mobile accounting application that can be implemented directly by MSMEs. Theoretically, this study enriches the literature on digital transformation in MSME accounting systems, while also serving as a basis for further development that includes data security features and artificial intelligence-based analytics.